2020
DOI: 10.1016/j.compositesb.2020.108442
|View full text |Cite
|
Sign up to set email alerts
|

Selective laser melting of Hastelloy X nanocomposite: Effects of TiC reinforcement on crack elimination and strength improvement

Abstract: The Hastelloy X (HX) nickel-based superalloy is increasingly applied in the aerospace industry because of its exceptional combination of oxidation resistance and hightemperature strength. The addition of nanoscale ceramic reinforcements to the HX alloy is expected to further improve its mechanical and thermophysical performance.The research challenge is to manufacture HX nanocomposites using additive manufacturing (AM) technologies, particularly selective laser melting (SLM), which has been used successfully t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…TiN nucleated preferentially during the in situ reactions between Ti/N due to its high melting point. The tendency to micro‐cracks of this coating was increased due to the excessive content of Si 3 N 4 19–21 . Figure 1D indicates that the micro‐crack can be observed in Ti 5 Si 3 with high hardness/brittleness in specimen 2.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…TiN nucleated preferentially during the in situ reactions between Ti/N due to its high melting point. The tendency to micro‐cracks of this coating was increased due to the excessive content of Si 3 N 4 19–21 . Figure 1D indicates that the micro‐crack can be observed in Ti 5 Si 3 with high hardness/brittleness in specimen 2.…”
Section: Resultsmentioning
confidence: 96%
“…The tendency to micro-cracks of this coating was increased due to the excessive content of Si 3 N 4 . [19][20][21] Figure 1D indicates that the micro-crack can be observed in Ti 5 Si 3 with high hardness/brittleness in specimen 2. The thermal/internal stress were produced due to uneven shrinkage/expansion of the mixed powders, exceeding the tensile strength limit under the actions of difference of temperature gradient and the thermal expansion coefficient in LIP.…”
Section: Resultsmentioning
confidence: 99%
“…The MGS was 97 nm. Such presence of nano-scale grains had a strong influence in enhancing the mechanical properties of the (SiC-AlN)/ZrB 2 composite [ 39 ]. When the temperature further increased, the elongated crystal grains further increased, and the MGS also increased with the temperature increase ( Figure 4 c,d).…”
Section: Resultsmentioning
confidence: 99%
“…It has been widely reported that the additively manufactured Ni-based metal matrix composites (MMC) can achieve partial CET with the presence of various ceramic particles. [25][26][27][28][29][30][31][32] Among these candidates, CoAl 2 O 4 is believed to be capable of triggering grain refinement in Ni-base superalloys by interacting with reactive elements such as Cr, Ti, and Nb in the melt pool and forming elemental Co. [33,34] Previous studies have shown that a subtle addition of CoAl 2 O 4 (e.g., 0.2 wt pct) contributes to refining the grain size and reducing the degree of elastic anisotropy within L-PBF processed Alloy 718 when optimized scan parameters and 67 degree of scan rotation were applied. [35,36] The resulting oxides distributed with the microstructure were also found to impede the movement of grain boundaries during heat treatment.…”
Section: Introductionmentioning
confidence: 99%